A retrospective study on the incidence of hypocalcemia and number of parathyroid glands identified and preserved during thyroid surgeries - J., Pauly T.; V., Santhosh P.; V., Santhosh T.; M., Vinodh (International Journal of Research in Medical Sciences, 2016)
Background: Hypocalcaemia remains a major post-operative complication of total thyroidectomy causing potentially severe symptoms and anxiety in affected patients and increasing hospitalization time. Therefore the present study was designed to evaluate the incidence of hypocalcaemia and the number of parathyroid gland. Methods: 146 patients who underwent total/near total thyroidectomy were recruited. The incidence of hypocalcaemia was analyzed with serial calcium estimation results with 6 hours, 24 hours, 48 hours and 2weeks post-operative calcium level estimations. The incidence of hypocalcaemia with regards to the number of parathyroid glands was determined and the results between the three groups were compared. Results: The overall incidence of hypocalcaemia decreases with increase in the number of parathyroid glands per operatively. In Group-3, 16% of patients had hypocalcaemia in first 6 hours and 96% of patients had calcium value more than 8 mg/dl after 2 weeks without the features of hypocalcaemia. It was 84% and 77% in Group-1, 33% and 23% in Group-2.The difference was found to be statistically significant (p<0.001). Conclusions: The incidence of hypocalcaemia decreases with increase in the number of parathyroid glands peroperativly in thyroid surgeries. The post-operative hypocalcaemia is predictable with the number of parathyroid glands and it gives a platform for an early discharge of the thyroidectomy patients without the fear of post-operative hypocalcaemia.